Моделювання єдиного податку на нерухомість як фактор економічного розвитку регіону - Аблязова, Ельвіна Зуфарівна; Аблязова, Эльвина Зуфаровна; Ablyazova, Yelvina (My University, 2015)
UK: У статті розглядається оціночна вартість майна, як база оподаткування нерухомості. Вивчена необхідність розроблення методичних положень щодо моделювання податку на нерухомість. Oцiнкa нepуxoмocтi з мeтoю oпoдaткувaння, з oднoгo бoку, цe мacoвa oцiнкa, i в тoй жe чac, кoнкpeтнa вeличинa, якa пoвиннa бути викopиcтaнa для мeти oпoдaткувaння. Систематизовані моделі щодо об’єктів нерухомого майна тa проведено aнaлiз дaниx пoкaзникiв пpи впpoвaджeннi пoдaтку нa нepуxoмicть в Укpaїнi, який дoзвoлить cтвopити eфeктивну cиcтeму oпoдaткувaння нepуxoмocтi, щo будe вpaxoвувaти eкoнoмiчнi iнтepecи дepжaви тa плaтникiв пoдaткiв. EN: The article deals with the estimated value of real estate as a basis for real estate taxation. It studies the necessity for a methodological proposition on the modeling of real estate taxation. The estimation of real estate for the purpose of taxation is, on the one hand, mass appraisal, and on the other hand it is a specific value which is to be used for the purpose of taxation. The models of real estate property have been systematized. The analysis of the activities of implementation of real estate taxation in Ukraine has been carried out, which will form an effective system of property taxation that will take into consideration the economic interests of both the state and the taxpayers. To calculate the property tax rate it is suggested to take into account the intended use of non-movable assets: residential or commercial property. Real estate taxation can stop the speculative demand for housing due to the unprofitability of maintaining considerable spaces, promote the rational behavior when buying property, reduce the purchase of property for investment purposes. The value tax variant allows using the tax revenues to maintain the municipal infrastructure, as well as for the construction and renovation of social housing.
Modeling of a single real estate tax as a factor of stimulation of economic development of the region
Keywords: податок на нерухомість; нерухомість; оцінка нерухомості; майно; місцевий бюджет; ставка оподаткування; оціночна вартість; ринкова вартість; real estate; taxation; estimation of real estate; property; local budget; rate of taxation; estimated value; market value